Pencegahan Peningkatan Angka Kejadian Penyakit Tidak Menular Pada Remaja Melalui Program Edukasi Terintegrasi di SMAN 2 Jorong - Anastasi Maratning; Margaretha Martini; Gertrudis Tutpai; Bernadetha Tri Handini; Maria Frani Ayu Andari Dias; Lanawati Lanawati; Aulia Rachman; Fransiska Dwi Hapsari; Ermeisi Er Unja (Universitas Maritim AMNI Semarang, 2024)
The phenomenon of non-communicable diseases not only affects adults but is also beginning to threaten the adolescent age group. Research shows that adolescents often do not realize that behaviors they consider normal, such as consuming sugary drinks, spending hours in front of screens, and lack of exercise, significantly contribute to the risk of NCDs later in life. This community service activity will be conducted using methods including a pre-test, lecture, group discussion, and post-test. Before the activity begins, a pre-test will be administered to the participants to assess their initial knowledge about preventing non-communicable diseases in adolescents. Following that, the lecture method will be used to educate the adolescents about the prevention of non-communicable diseases, such as hypertension, diabetes mellitus, and cholesterol, as well as their risk factors. After the lecture, a group discussion and Q&A session between the presenter and the participants will be conducted. A post-test will be administered again one week later to assess the effectiveness of the education. A significant result of this activity is the increase in students' knowledge regarding the prevention of NCDs.